Micropapillary colorectal carcinoma: clinical, pathological and molecular properties, including evidence of epithelial–mesenchymal transition. Issue 2 (28th October 2016) - Gonzalez, Raul S; Huh, Won Jae; Cates, Justin M M; Washington, Kay; Beauchamp, R Daniel; Coffey, Robert J; Shi, Chanjuan
Abstract : Aims: Colorectal carcinoma (CRC) with micropapillary (MP) features has only been described recently and is still being characterized. Methods and results: We reviewed the clinicopathological and molecular features of 42 CRC with MP features. Twenty‐nine cases were also evaluated for immunohistochemical evidence of epithelial–mesenchymal transition (EMT). The extent of MP features within our cohort ranged from 5% (13 cases) to 100% (one case). Twenty‐seven cases featured prominent cribriforming with dirty necrosis in the non‐MP component; nine displayed mucinous features. Twenty‐four of 29 cases (83%) demonstrated evidence of EMT. Thirty‐six cases (86%) showed advanced T‐category (pT3 or pT4), 31 (74%) had lymph node metastases and 23 (55%) had distant metastases. Median overall follow‐up was 36 months. Seventeen patients (40%) died of disease, with median survival of 23 months. Mutations were seen in 17 of 31 tested cases (55%), including 11 KRAS mutations and four BRAF V600E mutations. Microsatellite instability testing was performed on 21 cases; all were microsatellite‐stable. Compared to a cohort of 972 conventional CRC, MP CRC was more likely to present as stage IV disease ( P < 0.001), but patients with MP CRC showed no significant differences in overall survival after adjusting for stage. Conclusions: Micropapillary features in CRC portend a high likelihood of advanced local disease and distant metastases. MP CRC is often associated with a cribriform pattern elsewhere in the tumour and cystic nodal metastases with prominent necrosis. They also show frequent mutations in KRAS and BRAF . Immunohistochemical evidence of EMT is common in MP CRC.